Honeycomb structure
The honeycomb structure addresses issues of catalyst peeling and performance by optimizing porosity and pore distribution, ensuring effective catalyst support and enhanced purification and temperature-raising capabilities.
Patent Information
- Application Number
- JP2021056726
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-30
- Publication Date
- 2025-02-10
- Estimated Expiration
- 2041-03-30
AI Technical Summary
Conventional honeycomb structures face issues such as increased pressure loss, catalyst peeling, and reduced purification performance due to high catalyst loading, poor gas diffusivity, and inadequate temperature-raising performance when increasing catalyst support.
A honeycomb structure with specific porosity, pore distribution, and thickness of partition walls to support catalysts effectively, minimizing peeling and enhancing purification and temperature-raising performance.
The structure maintains catalyst adhesion and improves purification performance, especially at low temperatures, while maintaining mechanical strength.
Smart Images

Figure 0007628453000003 
Figure 0007628453000004 
Figure 0007628453000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a honeycomb structure, and more particularly to a honeycomb structure that can be particularly suitably used as a catalyst carrier for supporting a catalyst for purifying exhaust gas. [Background technology]
[0002] In recent years, awareness of environmental issues has been increasing throughout society. As a result, exhaust gas emissions from gasoline and diesel vehicles are regulated in each country, and various technologies for removing harmful components such as CO, HC, and NOx have been developed. When removing such harmful components from exhaust gas, a catalyst is generally used to cause a chemical reaction of the harmful components to change them into other relatively harmless components. For example, examples of catalysts for removing harmful components from exhaust gas include oxidation catalysts, three-way catalysts, and selective catalytic reduction catalysts for exhaust gas purification. A honeycomb structure is used as a catalyst carrier for supporting such exhaust gas purification catalysts.
[0003] Conventionally, as this honeycomb structure, one that includes a honeycomb structure part having porous partition walls that partition a plurality of cells that become a fluid flow path has been proposed (for example, see Patent Document 1). Then, the above-mentioned exhaust gas purification catalyst is supported (in other words, coated) on such a honeycomb structure, and an exhaust gas purification device for gasoline vehicles and diesel vehicles is manufactured. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2011-194342 A Summary of the Invention [Problem to be solved by the invention]
[0005] In order to comply with recent stricter exhaust gas emission regulations, it is necessary to increase the amount of catalyst supported on the honeycomb structure. However, when the amount of catalyst supported on the conventional honeycomb structure is increased, the following problems occur.
[0006] Conventional honeycomb structures have problems in that the cells serving as fluid flow paths are clogged with catalyst, increasing the pressure loss of the honeycomb structure, and in that when a large amount of catalyst is supported on the surfaces of the partition walls that divide the cells, the supported catalyst is easily peeled off from the surfaces of the partition walls.
[0007] Furthermore, since the partition walls constituting the honeycomb structure are formed of a porous material, when a catalyst is loaded on the partition walls, the catalyst is filled not only on the surface of the partition walls but also inside the pores of the porous partition walls. If the porosity of the partition walls is increased to load the catalyst in the pores in order to increase the amount of catalyst loaded, the gas diffusion through the pores of the partition walls is deteriorated, and the catalyst cannot be used effectively. For example, if the gas diffusion is deteriorated and the catalyst cannot be used effectively, the purification performance of the honeycomb structure loaded with a catalyst for purifying exhaust gas is reduced. Hereinafter, increasing the porosity of the partition walls of the honeycomb structure may be referred to as "increasing the porosity of the honeycomb structure" or "increasing the porosity of the partition walls."
[0008] In addition, there is a demand for improved temperature rise performance for the honeycomb structure as a catalyst carrier, in order to contribute to improved purification performance at low temperatures. For example, the porosity of the partition walls may be increased to reduce the weight of the honeycomb structure, or the opening ratio of the cells formed in the honeycomb structure may be increased. Hereinafter, increasing the opening ratio of the cells formed in the honeycomb structure may be referred to as "increasing the opening ratio" of the honeycomb structure. However, when the honeycomb structure is made lighter or has a higher opening ratio, the strength of the honeycomb structure itself is reduced, so there is a limit to the lighter weight and higher opening ratio of the honeycomb structure, and there are cases where a sufficient effect cannot be obtained in response to the demand for improved temperature rise performance. Furthermore, reducing the weight of the honeycomb structure is accompanied by a higher porosity of the partition walls, which may result in a decrease in the purification performance as described above.
[0009] The present invention has been made in consideration of the problems of the conventional techniques. According to the present invention, there is provided a honeycomb structure that can be particularly suitably used as a catalyst carrier for supporting a catalyst for purifying exhaust gas. In particular, the present invention provides a honeycomb structure in which the catalyst supported on the partition walls is not easily peeled off and which can improve the purification performance. [Means for solving the problem]
[0010] According to the present invention, there is provided a honeycomb structure as described below.
[0011] [1] A columnar honeycomb structure portion having porous partition walls that define a plurality of cells that serve as fluid flow paths extending from a first end surface to a second end surface, and an outer peripheral wall disposed so as to surround an outer periphery of the partition walls, The thickness of the partition wall is 50 to 132 μm, The porosity of the partition walls is 40 to 55%, an opening ratio of pores on a surface of the partition wall per unit surface area of the partition wall is 10 to 15%, The total opening area S of the pores on the surface of the partition wall all The opening area S of pores with an opening diameter of 10 μm or less0~10 Percentage of the ratio (S 0~10 / S all × 100%) is 90% or more.
[0012] [2] The total opening area S of the pores on the surface of the partition all The opening area S of pores with an opening diameter of 10 μm or less 0~10 Percentage of the ratio (S 0~10 / S all × 100%) is 94% or more.
[0013] [3] The total opening area S of the pores on the surface of the partition all The opening area S of the pores with an opening diameter of more than 10 μm and less than 20 μm 10~20 Percentage of the ratio (S 10~20 / S all × 100%) is 6% or less.
[0014] [4] The total opening area S of the pores on the surface of the partition all The opening area S of pores with an opening diameter of more than 20 μm 20~MAX Percentage of the ratio (S 20~MAX / S all 3. The honeycomb structure according to any one of the above [1] to [3], wherein the ratio of the surface roughness to the surface roughness (x100%) is less than 1%.
[0015] [5] The honeycomb structure according to any one of the above [1] to [4], which is a catalyst carrier for supporting an oxidation catalyst or a three-way catalyst for exhaust gas purification in the pores of the partition walls.
[0016] [6] The honeycomb structure according to any one of the above [1] to [4], wherein an oxidation catalyst or a three-way catalyst for purifying exhaust gas is supported in the pores of the partition walls, and a filling rate of the catalyst in the pores is 20 to 35%.
[0017] [7] The honeycomb structure according to any one of the above [1] to [4], which is a catalyst carrier for supporting a selective catalytic reduction catalyst for exhaust gas purification in the pores of the partition walls.
[0018] [8] The honeycomb structure according to any one of the above [1] to [4], wherein a selective catalytic reduction catalyst for exhaust gas purification is supported in the pores of the partition walls, and a filling rate of the catalyst in the pores is 20 to 35%. Effect of the Invention
[0019] The honeycomb structure of the present invention can be particularly suitably used as a catalyst carrier for supporting a catalyst for purifying exhaust gas, and has the effect that the catalyst supported on the partition walls is not easily peeled off and the purification performance can be improved. In particular, the honeycomb structure of the present invention has excellent temperature rise performance, and is expected to improve the purification performance at low temperatures. In other words, the honeycomb structure of the present invention can improve the "light-off performance", which is the temperature characteristic at which the purification performance of the catalyst supported on the honeycomb structure is expressed. [Brief description of the drawings]
[0020] [Figure 1] 1 is a perspective view showing an embodiment of a honeycomb structure of the present invention, as viewed from an inflow end face side. FIG. [Diagram 2] 2 is a plan view of the honeycomb structure shown in FIG. 1 as viewed from the inflow end face side. [Diagram 3] FIG. 3 is a cross-sectional view showing a schematic cross section taken along line AA' of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The following describes the embodiments of the present invention, but the present invention is not limited to the following embodiments. Therefore, it should be understood that the scope of the present invention includes any modifications and improvements to the following embodiments based on the ordinary knowledge of a person skilled in the art without departing from the spirit of the present invention.
[0022] (1) Honeycomb structure: 1 to 3, a first embodiment of a honeycomb structure of the present invention is a honeycomb structure 100 including a columnar honeycomb structure portion 4. The honeycomb structure portion 4 includes porous partition walls 1 that define a plurality of cells 2 that serve as fluid flow paths extending from a first end face 11 to a second end face 12, and an outer peripheral wall 3 disposed so as to surround the outer periphery of the partition walls 1.
[0023] Fig. 1 is a perspective view seen from the inflow end face side, which is a schematic diagram showing one embodiment of a honeycomb structure of the present invention. Fig. 2 is a plan view seen from the inflow end face side of the honeycomb structure shown in Fig. 1. Fig. 3 is a cross-sectional view showing a schematic diagram of the A-A' cross section in Fig. 2.
[0024] The honeycomb structure 100 can be suitably used as a purification member for purifying exhaust gas discharged from engines of automobiles such as gasoline vehicles and diesel vehicles. In particular, the honeycomb structure 100 can be suitably used as a catalyst carrier for supporting a catalyst for purifying exhaust gas.
[0025] In the honeycomb structure 100, the partition walls 1 constituting the honeycomb structure portion 4 are configured as follows. First, the thickness of the partition walls 1 is 50 to 132 μm, and the porosity of the partition walls 1 is 40 to 55%. The opening ratio of the pores on the surface of the partition walls 1 per unit surface area of the partition walls 1 is 10 to 15%. Furthermore, the total opening area S of the pores open on the surface of the partition walls 1 is 10 to 15%. all The opening area S of pores with an opening diameter of 10 μm or less 0~10 Percentage of the ratio (S 0~10 / S all ×100%) is 90% or more.
[0026] The honeycomb structure 100 configured as described above can be particularly suitably used as a catalyst carrier for supporting a catalyst for purifying exhaust gas, and has the effect that the catalyst supported on the partition walls 1 is unlikely to peel off and the purification performance can be improved. In particular, the honeycomb structure 100 of this embodiment has excellent temperature rise performance, and is expected to improve the purification performance at low temperatures. That is, the honeycomb structure 100 of this embodiment can improve the light-off performance, which is the temperature characteristic at which the purification performance of the catalyst supported on the honeycomb structure 100 is expressed.
[0027] As described above, the thickness of the partition walls 1 is 50 to 132 μm. If the thickness of the partition walls 1 is less than 50 μm, the mechanical strength of the honeycomb structure 100 decreases. On the other hand, if the thickness of the partition walls 1 exceeds 132 μm, the temperature rise performance of the honeycomb structure 100 decreases. The thickness of the partition walls 1 of the honeycomb structure 100 is not particularly limited, but is preferably 60 to 100 μm, and more preferably 70 to 90 μm. The thickness of the partition walls 1 can be measured using, for example, a scanning electron microscope or a microscope.
[0028] The porosity of the partition walls 1 is 40 to 55%, preferably 47 to 52%, and more preferably 48 to 50%. The porosity of the partition walls 1 is a value measured by mercury intrusion porosimetry. The porosity of the partition walls 1 can be measured, for example, using Autopore 9500 (product name) manufactured by Micromeritics. The porosity can be measured using a test piece obtained by cutting out a part of the partition walls 1 from the honeycomb structure 100. If the porosity of the partition walls 1 is less than 40%, the temperature rise performance of the honeycomb structure 100 decreases. On the other hand, if the porosity of the partition walls 1 exceeds 55%, the mechanical strength of the honeycomb structure 100 decreases.
[0029] The aperture ratio of the pores on the surface of the partition walls 1 per unit surface area of the partition walls 1 is 10 to 15%, preferably 11 to 14%, and more preferably 12 to 13%. The aperture ratio of the pores on the surface of the partition walls 1 can be measured by the following method. A photograph of the surface of the partition walls 1 is taken with a scanning electron microscope (SEM), and in the photographed image, the solid parts of the partition walls 1 and the pores are binarized with binarization software to calculate the area ratio of each. The percentage (%) of the ratio of the area of the pores to the total area of the surface of the partition walls 1 is the aperture ratio (%) of the pores on the surface of the partition walls 1. The above-mentioned measurement of the aperture ratio of the pores on the surface of the partition walls 1 can be performed using a test piece obtained by cutting out a part of the partition walls 1 from the honeycomb structure 100. If the aperture ratio of the pores on the surface of the partition walls 1 is less than 10%, the filling rate of the catalyst in the pores of the partition walls 1 becomes low when the honeycomb structure 100 is used as a catalyst carrier. On the other hand, if the opening ratio of the pores on the surface of the partition walls 1 exceeds 15%, the temperature rise performance of the honeycomb structure 100 decreases.
[0030] The total opening area S of the pores on the surface of the partition wall 1 all The opening area S of pores with an opening diameter of 10 μm or less 0~10 Percentage of the ratio (S 0~10 / S all × 100%) is 90% or more. Hereinafter, the total opening area S all The opening area S of pores with an opening diameter of 10 μm or less 0~10 Percentage of the ratio (S 0~10 / S all× 100%)" is sometimes referred to as "the opening area ratio of pores having an opening diameter of 10 μm or less". If the opening area ratio of pores having an opening diameter of 10 μm or less is less than 90%, the catalyst supported on the partition wall 1 is less likely to peel off. In addition, the temperature rise performance of the honeycomb structure 100 is reduced, and the purification performance of the catalyst supported on the honeycomb structure 100 may not be fully exhibited. The opening area ratio of pores having an opening diameter of 10 μm or less is preferably 94% or more. There is no particular upper limit to the opening area ratio of pores having an opening diameter of 10 μm or less, and it is, for example, 98% or less. For this reason, it can be said that the opening area ratio of pores having an opening diameter of 10 μm or less is preferably 90 to 97%, and more preferably 94 to 96%. The opening area ratio of pores having an opening diameter of 10 μm or less can be measured by the following method.
[0031] First, let us consider the total opening area of the pores, S all " and "The opening area S of pores with an opening diameter of 10 μm or less 0~10 " is measured as follows. A photograph of the surface of the partition walls 1 is taken with a scanning electron microscope (SEM), and in the photographed image, the solid parts and pores of the partition walls 1 are binarized with binarization software, and the area ratio of each is calculated. A more detailed measurement method is as follows.
[0032] First, the honeycomb structure 100 is cut parallel to the extending direction of the cells 2 so that the partition wall 1 surface of the honeycomb structure 100 can be observed. Next, an image of the partition wall 1 surface is captured by a backscattered electron (annular detector) of a scanning electron microscope "S-3200N (product name): manufactured by HITACHI Corporation." The range in which the partition wall 1 surface is captured (image processing range) is the partition wall 1 surface between two partition walls 1 arranged vertically to the surface to be captured. Such a partition wall 1 surface is captured in a field of view of 20 points at a magnification of 100 times and within a range of 1200 × 1000 μm using a scanning electron microscope (hereinafter also referred to as "SEM").
[0033] Next, the obtained image is subjected to a binarization process by taking the difference between the original image and the smoothed image, and setting a brightness of 20 as a threshold value in the difference image. Binarization process in which such a threshold value is set is sometimes called a dynamic threshold method. This binarization process makes it possible to extract the openings of the pores (in other words, the voids on the surface of the partition wall 1) in the obtained image. The image after the binarization process described above is called the "analysis area."
[0034] Next, an inscribed circle with a diameter of 10 μm or less is fitted to the "analysis region". At this time, the inscribed circle is not overlapped with the substantial part of the partition wall 1. When the inscribed circle is fitted, the position of the inscribed circle is specified as a coordinate. When fitting the inscribed circle with a diameter of 10 μm or less, an inscribed circle with a diameter of 10 μm or less and a maximum diameter is fitted so that the substantial part of the partition wall 1 and the inscribed circle do not overlap. In addition, the diameter of this inscribed circle (i.e., an inscribed circle with a diameter of 10 μm or less and a maximum diameter) is calculated, and the area of the inscribed circle is calculated from the diameter of the inscribed circle. As for the position of the inscribed circle, it is preferable to determine the X coordinate and the Y coordinate of the center of the inscribed circle by defining the X axis and the Y axis in the image. The part (pore) to which the inscribed circle is fitted is defined as "a pore in which an inscribed circle with a maximum diameter of 10 μm or less is drawn in the opening region". Then, this "pore in which an inscribed circle with a maximum diameter of 10 μm or less is drawn within the opening region" is defined as a "pore with an opening diameter of 10 μm or less."
[0035] Next, a process is performed to further remove the fitted inscribed circle from the "analysis area". After that, an inscribed circle with a diameter of 10 μm or less is fitted again to the analysis area (analysis area from which the inscribed circle has been removed) in the same manner as described above, and if an inscribed circle is fitted, the coordinates of the position of this inscribed circle are identified, and the area of the inscribed circle is calculated from the diameter of this inscribed circle. This process is repeated until an "inscribing circle with a diameter of 10 μm or less" can no longer be fitted.
[0036] By the above operations, all inscribed circles drawn within the pores in the image that have a diameter of 10 μm or less are found, and the areas of the inscribed circles obtained are added to calculate the "sum of the areas of inscribed circles with a diameter of 10 μm or less." The calculated "sum of the areas of inscribed circles with a diameter of 10 μm or less" is then calculated as the "opening area S of pores with an opening diameter of 10 μm or less." 0~10 "
[0037] In addition, the total opening area of the pores S all " can be calculated from the image that has been binarized as described above. Specifically, the "opening area S of pores with an opening diameter of 10 μm or less in the "analysis region" is calculated by the method described above. 0~10 " is obtained, an inscribed circle with a diameter of more than 10 μm is fitted to the "analysis region". The portion into which the inscribed circle with a diameter of more than 10 μm is fitted is regarded as a "pore in which an inscribed circle with a maximum diameter of more than 10 μm is drawn within the opening region", and the pore is regarded as a "pore with an opening diameter of more than 10 μm". When an inscribed circle with a diameter of more than 10 μm is fitted, the coordinates of the position of the inscribed circle are identified, and the area of the inscribed circle is calculated from the diameter of the inscribed circle. Next, a process is performed to further remove the fitted inscribed circle from the "analysis region". After that, an inscribed circle with a diameter of more than 10 μm is fitted again to the analysis region (analysis region from which the inscribed circle has been removed) in the same manner as described above, and when an inscribed circle is fitted, the coordinates of the position of the inscribed circle are identified, and the area of the inscribed circle is calculated from the diameter of the inscribed circle. This is then repeated until an "inscribing circle with a diameter of more than 10 μm" can no longer be fitted, and then an inscribing circle with a diameter of 10 μm or less is fitted to that analysis area (analysis area excluding the inscribing circle), and this is repeated until that inscribing circle can no longer be fitted. Through the above operations, all inscribing circles drawn within the pores in the image are found, and the areas of the obtained inscribing circles are added together to calculate the "sum of the areas of pores with an opening diameter of more than 10 μm." The calculated "sum of the areas of inscribing circles with a diameter of more than 10 μm" is then used as the "opening area S of pores with an opening diameter of more than 10 μm." 10~MAX The "opening area S of pores with an opening diameter of 10 μm or less" calculated as above is 0~10 " and the previously calculated "opening area S of pores with an opening diameter of more than 10 μm 10~MAX" is the sum of "total opening area of the pores S all " In addition, "the total opening area of the pores S all In calculating ", for example, by applying an inscribed circle having a diameter of more than 10 μm and less than 20 μm according to the above-mentioned method, the opening area S of the pores having an opening diameter of more than 10 μm and less than 20 μm is calculated. 10~20 " can be calculated. Furthermore, by applying an inscribed circle of more than 20 μm to the "analysis region" after that, "the opening area S of the pores with an opening diameter of more than 20 μm can be calculated. 20~MAX " can be calculated.
[0038] In the honeycomb structure 100, the opening area ratio of pores having an opening diameter of 10 μm or less is 90% or more, and the opening area ratio of pores having an opening diameter of more than 10 μm is 10% or less. Here, although not particularly limited, the total opening area S of the pores open on the surface of the partition wall 1 all The opening area S of the pores with an opening diameter of more than 10 μm and less than 20 μm 10~20 Percentage of the ratio (S 10~20 / S all × 100%) is preferably 10% or less, and more preferably 6% or less. By configuring in this way, the catalyst supported on the partition walls is less likely to peel off, and the purification performance can be further improved. Hereinafter, "the total opening area S of the pores that open on the surface of the partition walls 1" will be referred to as "the total opening area S of the pores that open on the surface of the partition walls 1". all The opening area S of the pores with an opening diameter of more than 10 μm and less than 20 μm 10~20 Percentage of the ratio (S 10~20 / S all × 100%) is sometimes referred to as the "opening area rate of pores with an opening diameter of 10 to 20 μm."
[0039] In addition, the total opening area S of the pores open on the surface of the partition wall 1 all The opening area S of pores with an opening diameter of more than 20 μm 20~MAX Percentage of the ratio (S 20~MAX / S all× 100%) is preferably less than 1%, and more preferably is a value equal to or less than the practical measurement limit. By configuring in this way, the catalyst supported on the partition walls is less likely to peel off, and the purification performance can be further improved. Hereinafter, "the total opening area S of the pores that open on the surface of the partition walls 1" will be referred to as all The opening area S of pores with an opening diameter of more than 20 μm 20~MAX Percentage of the ratio (S 20~MAX / S all × 100%) is sometimes referred to as the "opening area rate of pores with an opening diameter of more than 20 μm."
[0040] The average pore diameter of the partition walls 1 is not particularly limited, but for example, the average pore diameter of the partition walls 1 is preferably 3 to 12 μm, more preferably 4 to 10 μm, and particularly preferably 5 to 8 μm. The average pore diameter of the partition walls 1 is a value measured by mercury intrusion porosimetry. The average pore diameter of the partition walls 1 can be measured using, for example, Autopore 9500 (product name) manufactured by Micromeritics. The average pore diameter can be measured using the above-mentioned test piece for measuring porosity.
[0041] There is no particular limitation on the shape of the cells 2 formed in the honeycomb structure portion 4. For example, examples of the shape of the cells 2 in a cross section perpendicular to the extending direction of the cells 2 include polygonal, circular, and elliptical shapes. Examples of polygonal shapes include triangular, rectangular, pentagonal, hexagonal, and octagonal shapes. The shape of the cells 2 is preferably triangular, rectangular, pentagonal, hexagonal, or octagonal. Regarding the shape of the cells 2, all the cells 2 may have the same shape or different shapes. For example, although not shown in the figure, a mixture of rectangular cells and octagonal cells may be used. Regarding the size of the cells 2, all the cells 2 may have the same size or different sizes. For example, although not shown in the figure, the size of some of the multiple cells may be large, and the size of the other cells may be relatively small. In the present invention, the cell 2 means a space surrounded by the partition wall 1.
[0042] The cell density of the cells 2 partitioned and formed by the partition walls 1 is not particularly limited. For example, the cell density of the honeycomb structure portion 4 is 31 to 93 cells / cm. 2 is preferably 45 to 62 pieces / cm 2 If the cell density is too small, the purification performance may decrease when the honeycomb structure 100 is used as a catalyst carrier. On the other hand, if the cell density is too large, the pressure loss during use may increase.
[0043] The outer peripheral wall 3 of the honeycomb structure portion 4 may be integrally formed with the partition wall 1, or may be an outer peripheral coating layer formed by applying an outer peripheral coating material to the outer peripheral side of the partition wall 1. For example, although not shown in the drawings, the outer peripheral coating layer can be provided on the outer peripheral side of the partition wall after the partition wall and the outer peripheral wall are integrally formed during production and then the formed outer peripheral wall is removed by a known method such as grinding.
[0044] There is no particular limitation on the shape of the honeycomb structure part 4. Examples of the shape of the honeycomb structure part 4 include a columnar shape such as a circle, an ellipse, or a polygon, in which the first end face 11 (e.g., an inflow end face) and the second end face 12 (e.g., an outflow end face) have a circular, elliptical, or polygonal shape.
[0045] There is no particular limitation on the size of the honeycomb structure part 4, for example, the length from the first end face 11 to the second end face 12, and the size of a cross section perpendicular to the extension direction of the cells 2 of the honeycomb structure part 4. Each size may be appropriately selected so as to obtain optimal purification performance when the honeycomb structure 100 is used as a filter for purifying exhaust gas.
[0046] There is no particular limitation on the material of the partition walls 1. Examples of the material of the partition walls 1 include ceramics. More specifically, examples of the material of the partition walls 1 include cordierite, mullite, alumina, and SiC.
[0047] In the honeycomb structure 100, a catalyst for purifying exhaust gas may be supported on the partition walls 1 that define the plurality of cells 2. Supporting a catalyst on the partition walls 1 means that the surfaces of the partition walls 1 and the inner walls of the pores formed in the partition walls 1 are coated with the catalyst. With this configuration, CO, NOx, HC, and the like in the exhaust gas can be converted into harmless substances by catalytic reaction. For example, examples of catalysts for purifying exhaust gas include oxidation catalysts, selective catalytic reduction catalysts, and three-way catalysts.
[0048] The oxidation catalyst may be a catalyst containing a precious metal. Specific examples of the oxidation catalyst include those containing at least one selected from the group consisting of platinum (Pt), palladium (Pd) and rhodium (Rh). When the oxidation catalyst is supported on the partition wall 1, the amount of the oxidation catalyst supported is preferably 50 to 150 g / L. Here, the amount of the catalyst supported (g / L) refers to the amount (g) of the catalyst supported per unit volume (1 L) of the honeycomb structure portion 4.
[0049] A three-way catalyst is a catalytic converter that mainly converts hydrocarbons (HC), carbon monoxide (CO), and nitrogen oxides (NO X The term "three-way catalyst" refers to a catalyst that purifies the above-mentioned substances. Examples of three-way catalysts include catalysts containing platinum (Pt), palladium (Pd), and rhodium (Rh). The amount of the three-way catalyst supported is preferably 150 to 300 g / L.
[0050] When an oxidation catalyst or a three-way catalyst for purifying exhaust gas is supported in the pores of the partition walls 1, the filling rate of the catalyst in the pores of the partition walls 1 is preferably 20 to 35%, and more preferably 25 to 30%. Here, the filling rate of the catalyst in the pores of the partition walls 1 can be measured by the following method. A photograph of a cross section of the partition walls 1 is taken with a scanning electron microscope (SEM), and in the photographed image, the solid parts of the partition walls 1, the pores, and the catalyst are ternarized with image software, and the filling area ratio of the catalyst in the pores of the partition walls 1 is calculated.
[0051] The selective catalytic reduction catalyst is a catalyst that selectively reduces the components to be purified. Hereinafter, the selective catalytic reduction catalyst is also referred to as an "SCR catalyst." "SCR" is an abbreviation for "Selective Catalytic Reduction." The selective catalytic reduction catalyst is preferably a zeolite-type selective catalytic reduction catalyst or a vanadium-type selective catalytic reduction catalyst. The zeolite-type selective catalytic reduction catalyst refers to a catalyst that contains a catalytically active component that contains zeolite. As the zeolite-type selective catalytic reduction catalyst, for example, a selective catalytic reduction catalyst that contains a metal-substituted zeolite can be mentioned. As the metal that substitutes the zeolite, iron (Fe) and copper (Cu) can be mentioned. The vanadium-type selective catalytic reduction catalyst refers to a catalyst that contains a catalytically active component that contains vanadium. As the vanadium-type selective catalytic reduction catalyst, for example, a catalyst that contains vanadium or tungsten as a main component can be mentioned. The amount of the selective catalytic reduction catalyst supported is preferably 100 to 250 g / L.
[0052] When a selective catalytic reduction catalyst for exhaust gas purification is supported in the pores of the partition walls 1, the loading rate of the catalyst in the pores of the partition walls 1 is preferably 20 to 35%, and more preferably 25 to 30%. The loading rate of the catalyst in the pores of the partition walls 1 can be measured by the above-mentioned measurement method.
[0053] (2) Manufacturing method of honeycomb structure: The manufacturing method of the honeycomb structure 100 of the present embodiment shown in Figs. 1 to 3 is not particularly limited, and can be manufactured by, for example, the following method. First, a plastic clay for manufacturing a honeycomb structure part is prepared. The clay for manufacturing a honeycomb structure part can be prepared by adding additives such as binders, a pore former, and water to a material selected from the above-mentioned suitable materials for the honeycomb structure part as a raw material powder. An example of the raw material powder is a cordierite raw material. The cordierite raw material is a raw material that becomes cordierite by firing, and specifically, is a raw material that is blended to have a chemical composition in the range of 42 to 56 mass % of silica, 30 to 45 mass % of alumina, and 12 to 16 mass % of magnesia.
[0054] Examples of the pore former include polymers such as polyacrylic acid-based polymers, starch, foamed resins, and polymethyl methacrylate (PMMA), as well as coke. In particular, it is preferable to use polyacrylic acid-based polymers as the pore former. Examples of the binder include organic binders such as methyl cellulose, hydroxypropoxyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose, and polyvinyl alcohol. In particular, it is preferable to use methyl cellulose and hydroxypropoxyl cellulose in combination as the binder. Examples of the surfactant include, but are not limited to, ethylene glycol, dextrin, fatty acid soap, and polyalcohol. These can be used alone or in combination of two or more. The content of the surfactant is not particularly limited, but is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, relative to 100 parts by mass of the cordierite-forming raw material, and can be, for example, 0.5 to 2 parts by mass.
[0055] In preparing the clay, the porosity of the partition walls can be adjusted by adjusting the amount of the pore former added. In addition, in order to adjust the opening ratio of the pores on the surface of the partition walls and the opening area ratio of the pores with an opening diameter of 10 μm or less, it is preferable to adjust the particle diameter of the raw material silica. For example, it is preferable to prepare the clay using silica with a particle diameter of 10 μm or less.
[0056] Next, the clay thus obtained is extrusion-molded to produce a columnar honeycomb formed body having partition walls which define a plurality of cells, and an outer peripheral wall disposed so as to surround the partition walls.
[0057] Next, the obtained honeycomb molded body is dried, for example, by microwaves and hot air. Next, the honeycomb molded body is fired to manufacture a honeycomb structure. The firing temperature and firing atmosphere vary depending on the raw materials, and a person skilled in the art can select the firing temperature and firing atmosphere optimal for the selected materials. In this manner, the honeycomb structure of this embodiment can be manufactured. EXAMPLES
[0058] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0059] Example 1 Talc, kaolin, alumina, aluminum hydroxide, and porous silica were prepared as cordierite raw materials. The amounts of the raw materials were 41% by mass of talc, 13% by mass of kaolin, 13% by mass of calcined kaolin, 12% by mass of alumina, 12% by mass of aluminum hydroxide, 8% by mass of fused silica, and 1% by mass of crystalline silica.
[0060] Next, 2.2 parts by mass of a pore former, 8.0 parts by mass of a binder, 1.1 parts by mass of a surfactant, and 48 parts by mass of water were added to 100 parts by mass of the cordierite raw material to prepare a clay. A polyacrylic acid-based polymer was used as the pore former. Methyl cellulose was used as the binder. Ethylene glycol was used as the surfactant.
[0061] Next, the obtained clay was molded using an extrusion molding machine to produce a honeycomb molded body. Next, the obtained honeycomb molded body was dried by high-frequency dielectric heating, and then further dried using a hot air dryer. The shape of the cells in the honeycomb molded body was rectangular.
[0062] Next, both end faces of the honeycomb formed body were cut to have a predetermined size. Next, the dried honeycomb formed body was degreased and fired to manufacture the honeycomb structure of Example 1.
[0063] The honeycomb structure of Example 1 had an end face diameter of 266.7 mm and an overall length in the cell extension direction of 101.6 mm. The diameter and overall length of the honeycomb structure are shown in Table 1. The honeycomb structure of the honeycomb structure had a partition wall thickness of 0.114 mm and a cell density of 62.0 cells / cm. 2 The porosity of the partition walls was 45%. The results are shown in Table 1. The porosity of the partition walls was measured using an Autopore 9500 (product name) manufactured by Micromeritics. In measuring the porosity, a part of the partition wall was cut out from the honeycomb structure to prepare a test piece, and the porosity was measured using the obtained test piece. The test piece was a rectangular parallelepiped with length, width, and height of approximately 10 mm, approximately 10 mm, and approximately 20 mm, respectively. The test piece was taken from near the center in the axial direction of the honeycomb structure.
[0064] For the honeycomb structure of Example 1, the aperture ratio of the pores on the surface of the partition wall per unit surface area of the partition wall was measured by the following method. The aperture ratio of the pores on the surface of the partition wall was 13.2%. The results are shown in the "Aperture ratio of pores (%)" column in Table 1.
[0065] [Opening rate of pores on the partition surface (%)] A photograph of the partition wall surface was taken with a scanning electron microscope (SEM), and in the photographed image, the solid parts of the partition wall and the pores were binarized with binarization software to calculate the area ratio of each. The percentage (%) of the ratio of the area of the pores to the total area of the partition wall surface was defined as the opening rate (%) of the pores on the partition wall surface.
[0066] For the honeycomb structure of Example 1, the "open area ratio of pores having an opening diameter of 10 μm or less," "open area ratio of pores having an opening diameter of 10 to 20 μm," and "open area ratio of pores having an opening diameter of more than 20 μm" were measured by the following method. The results are shown in Table 1.
[0067] [Opening area ratio (%) of pores with an opening diameter of 10 μm or less, Opening area ratio (%) of pores with an opening diameter of 10 to 20 μm, Opening area ratio (%) of pores with an opening diameter of more than 20 μm] A photograph of the partition wall surface was taken with a scanning electron microscope (SEM), and in the photographed image, the solid part of the partition wall and the pores were binarized with binarization software, and the area ratio of each was calculated. The areas of the pores with an opening diameter of 10 μm or less, the pores with an opening diameter of 10 to 20 μm, and the pores with an opening diameter of more than 20 μm were calculated by applying an inscribed circle with a diameter corresponding to each opening diameter in image analysis, and calculating the area of the inscribed circle from the diameter of each inscribed circle. Specifically, as described in the above-mentioned embodiment, first, the difference between the original image and the smoothed image obtained was taken, and the difference image was binarized with a brightness of 20 as a threshold value to obtain an analysis region. The inscribed circle with a diameter of 10 μm or less, the inscribed circle with a diameter of more than 10 μm, the inscribed circle with a diameter of 20 μm or less, and the inscribed circle with a diameter of more than 20 μm were sequentially applied to the analysis region obtained in this manner, and the area of each inscribed circle was calculated from the diameter of each inscribed circle. Then, the opening area of pores with an opening diameter of 10 μm or less, the opening area of pores with an opening diameter of 10 to 20 μm, and the opening area of pores with an opening diameter of more than 20 μm were determined, and their ratio (opening area rate (%)) was calculated.
[0068] [Table 1]
[0069] A catalyst was supported on the partition walls of the honeycomb structure of Example 1 by the following method. First, a catalyst slurry containing an oxidation catalyst was prepared. Specifically, a Pt-containing nitric acid solution was added to and mixed with alumina powder, and then the mixture was baked in a furnace at 400°C. Then, water and alumina sol were added to the obtained powder to prepare a catalyst slurry. Next, the obtained catalyst slurry was supported on the honeycomb structure so that the amount of catalyst supported per unit volume after drying was 100g / L. In supporting the catalyst, the honeycomb structure was dipped, and excess catalyst slurry was blown off with air to be impregnated. Then, the honeycomb structure was dried at a temperature of 150°C, and further heat-treated at 400°C for 2 hours, thereby obtaining a catalyst-supported honeycomb structure. The amount of catalyst supported on the honeycomb structure of Example 1 was 100g / L.
[0070] The catalyst loading state of the catalyst-loaded honeycomb structure was confirmed by SEM. When the catalyst was loaded on the partition walls on the substrate, it was marked "On-wall" in the "Catalyst Loading State" column of Table 2. Furthermore, when the catalyst was loaded in the pores on the partition walls, it was marked "IN-wall" in the "Catalyst Loading State" column of Table 2.
[0071] The catalyst loading rate (%) of the partition walls of the catalyst-supporting honeycomb structure was measured as catalyst area / pore area by calculating the areas of the catalyst, substrate, and pores from SEM photographs. The measurement results are shown in Table 2.
[0072] The catalyst-supported honeycomb structure was evaluated for "isostatic strength (MPa)," "HC purification performance (%)," "light-off performance (1)," "light-off performance (2)," "PD," "purification performance after HVT (%)," "mass after HVT (%)," and "presence or absence of catalyst peeling." The evaluation methods are as follows. The results are shown in Table 2.
[0073] [Isostatic strength (MPa)] The measurement of isostatic strength was performed based on the isostatic fracture strength test stipulated in M505-87 of the automobile standard (JASO standard) issued by the Society of Automotive Engineers of Japan. The isostatic fracture strength test is a test in which a honeycomb structure is placed in a cylindrical rubber container, covered with an aluminum plate, and isotropically compressed in water. In other words, the isostatic fracture strength test is a test that simulates the compressive load applied when the honeycomb structure is gripped at its outer periphery by a can body. The isostatic strength measured by this isostatic fracture strength test is indicated by the pressurized pressure value (MPa) at which the honeycomb structure breaks. In the evaluation of isostatic strength, a value of 1.0 MPa or more is considered to be a pass.
[0074] [HC purification performance (%)] In the measurement of the HC purification performance, first, a test gas containing HC was flowed into a catalyst-supported honeycomb structure (hereinafter, simply referred to as a "catalyst-supported honeycomb structure") supporting the above-mentioned catalyst. Then, the amount of NOx in the exhaust gas discharged from the catalyst-supported honeycomb structure was analyzed by a gas analyzer. The temperature of the test gas flowing into the catalyst-supported honeycomb structure was set to 200°C. The temperature of the catalyst-supported honeycomb structure and the test gas were adjusted by a heater. An infrared image furnace was used as the heater. The test gas used was a gas obtained by mixing 300 ppm of HC (propylene 80% + propane 20%), 5 vol. % of carbon dioxide, 1000 ppm of carbon monoxide, 8 vol. % of oxygen, 1000 ppm of nitric oxide (volume basis) and 5 vol. % of water in nitrogen. As for the test gas, a mixed gas containing water and other gases was prepared separately, and these were mixed in a pipe when the test was performed. The gas analyzer used was "MEXA9100EGR (product name) manufactured by HORIBA Corporation." The space velocity when the test gas flows into the catalyst-supported honeycomb structure is 120,000 (hr. -1 ) was decided.
[0075] [Light-off performance (1)] The engine was accelerated and exhaust gas was passed through the catalyst-supported honeycomb structure at 300° C. until the temperature reached 600° C. At that time, the time (seconds) until the internal temperature of the catalyst-supported honeycomb structure reached 550° C. was measured, and the time (seconds) required to reach 550° C. was used as the evaluation result of light-off performance (1).
[0076] [Light-off performance (2)] The engine was accelerated and exhaust gas was passed through the catalyst-supported honeycomb structure of each Example until it reached 600°C. At that time, the internal temperature (°C) was measured. Moreover, for the catalyst-supported honeycomb structure of Comparative Example 1 described below, the carrier was heated in a similar manner and the internal temperature (°C) was measured. The temperature difference (°C) between the catalyst-supported honeycomb structure of each Example and the catalyst-supported honeycomb structure of Comparative Example 1 was calculated, and the calculated temperature difference (°C) was used as the evaluation result of the light-off performance (2).
[0077] [PD] PD stands for pressure loss. PD is evaluated at room temperature (25℃) at 11m 3 Air was passed through the catalyst-supporting honeycomb structure at a flow rate of 1 / min. In this state, the difference in pressure between the air inlet side and the air outlet side was measured. This pressure difference was calculated as the pressure loss.
[0078] [Post-HVT purification performance (%)] HVT stands for superheat vibration test. The evaluation of purification performance after HVT is performed by applying vibrations in the direction of the exhaust gas flow while flowing high-temperature combustion gas through a catalyst-supported honeycomb structure. In the evaluation of purification performance after HVT, if there are no cracks before or after the test, it is considered to have passed.
[0079] [Mass after HVT (%)] HVT stands for overheat vibration test. Mass after HVT is evaluated by applying vibration in the direction of the exhaust gas flow while flowing high-temperature combustion gas through a catalyst-supported honeycomb structure, and confirming that there is no change in mass due to catalyst peeling before and after the test. In the evaluation of purification performance after HVT, a product is considered to have passed if the mass difference before and after the test is 1% or less.
[0080] [Catalyst peeling] First, the catalyst-supported honeycomb structure of each example is blown with air at 0.2 MPaG to remove the catalyst that is not fixed to the honeycomb structure. Next, the mass of the catalyst-supported honeycomb structure after air blowing is measured. The measured mass is defined as "initial mass W1". Next, pure water is poured into a beaker so that the catalyst-supported honeycomb structure is sufficiently immersed, and the catalyst-supported honeycomb structure that has been blown with air is gently placed therein. The beaker is placed in an ultrasonic cleaner, and the catalyst-supported honeycomb structure in the beaker is vibrated at an oscillation frequency of 38 to 45 kHz for 30 minutes. Next, the catalyst-supported honeycomb structure is taken out of the ultrasonic cleaner, and washed by moving it up and down in a beaker containing pure water for 10 seconds. The catalyst-supported honeycomb structure thus washed is taken out of the beaker, and after removing the moisture adhering to the catalyst-supported honeycomb structure, it is dried at 200°C for one hour. Then, the mass (mass after evaluation) of the dried catalyst-supported honeycomb structure is measured. Here, the mass after the above-mentioned evaluation is defined as "mass after evaluation W2". Then, the "mass reduction rate" of the catalyst-supported honeycomb structure due to catalyst peeling was calculated using formula (1): Mass reduction rate (%) = (W1 - W2) / W1 x 100%, and the presence or absence of catalyst peeling was confirmed using the following evaluation criteria. If the mass reduction rate was 1.0% or more, it was determined that catalyst peeling was present, and "Present" was recorded in the "Presence or absence of catalyst peeling" column in Table 2. On the other hand, if the mass reduction rate was less than 1.0%, it was determined that catalyst peeling was not present, and "Absent" was recorded in the "Presence or absence of catalyst peeling" column in Table 2.
[0081] [Table 2]
[0082] (Examples 2 to 9) In Examples 2 to 9, honeycomb structures were manufactured in the same manner as in Example 1, except that the raw materials and die were changed from those in Example 1. Specifically, in Example 2, the thickness of the partition wall was reduced from 0.114 mm to 0.089 mm. In Example 3, the thickness of the partition wall was increased from 0.114 mm to 0.132 mm. In Example 4, the porosity was changed to 50%. In Example 5, the porosity was changed to 47%. In Example 6, the thickness of the partition wall was changed from 0.114 mm to 0.064 mm. In Example 7, the porosity was changed to 47%. In Example 8, the porosity was set to 45%. In Example 9, the porosity was changed to 50%.
[0083] (Comparative Examples 1 to 2) In Comparative Examples 1 and 2, honeycomb structures were manufactured in the same manner as in Example 1, except that the recipes for the pore-forming material and the like were changed from those in Example 1. Specifically, in Comparative Example 1, the particle size of the pore-forming material was changed to 5 μm. In Comparative Example 2, the particle size of the pore-forming material was changed to 20 μm.
[0084] For the honeycomb structures of Examples 2 to 9 and Comparative Examples 1 and 2, the properties shown in each column of Table 1 were measured in the same manner as in Example 1. The results are shown in Table 1.
[0085] A catalyst was supported on the honeycomb structures of Examples 2 to 9 and Comparative Examples 1 and 2 in the same manner as in Example 1, and measurements and evaluations were carried out on the properties shown in each column of Table 2. The results are shown in Table 2.
[0086] (result) The honeycomb structures of Examples 1 to 9 were able to obtain good results in each evaluation, as shown in Table 2. On the other hand, in the honeycomb structure of Comparative Example 1, catalyst peeling was confirmed in the evaluation of the presence or absence of catalyst peeling, and the honeycomb structure of Comparative Example 2 did not satisfy the pass standard in the evaluation of HC purification performance. [Industrial Applicability]
[0087] The honeycomb structure of the present invention can be used as a catalyst carrier for supporting a catalyst for purifying exhaust gas. [Explanation of symbols]
[0088] 1: partition wall, 2: cell, 3: outer peripheral wall, 4: honeycomb structure portion, 11: first end face, 12: second end face, 100: honeycomb structure.
Claims
1. a columnar honeycomb structure having porous partition walls made of cordierite that define a plurality of cells serving as fluid flow paths extending from a first end surface to a second end surface, and an outer peripheral wall disposed so as to surround an outer periphery of the partition walls; The thickness of the partition wall is 50 to 132 μm, The porosity of the partition wall is 40 to 55%, an opening ratio of pores on a surface of the partition wall per unit surface area of the partition wall is 10 to 15%, A honeycomb structure in which the ratio of the opening area S0-10 of pores having an opening diameter of 10 μm or less to the total opening area Sall of the pores open on the surface of the partition walls is 90% or more (S0-10 / Sall×100%).
2. The honeycomb structure according to claim 1, wherein the ratio of the opening area S0 to S10 of pores having an opening diameter of 10 μm or less to the total opening area Sall of the pores opening on the surface of the partition wall is 94% or more (S0 to S10 / Sall×100%).
3. The honeycomb structure according to claim 1 or 2, wherein the ratio of the opening area S10 to S20 of pores having an opening diameter of more than 10 μm and not more than 20 μm to the total opening area Sall of the pores opening on the surface of the partition wall is 6% or less (S10 to S20 / Sall × 100%).
4. The percentage of the ratio of the opening area S20-MAX of pores having an opening diameter of more than 20 μm to the total opening area Sall of the pores open on the surface of the partition wall (S20-MAX / Sall×100%) The honeycomb structure according to any one of claims 1 to 3, wherein the ratio of the surface area to the surface area is less than 1%.
5. 5. The honeycomb structure according to claim 1, which is a catalyst carrier for supporting an oxidation catalyst or a three-way catalyst for purifying exhaust gas in the pores of the partition walls.
6. 5. The honeycomb structure according to claim 1, wherein an oxidation catalyst or a three-way catalyst for purifying exhaust gas is supported in the pores of the partition walls, and a filling rate of the catalyst in the pores is 20 to 35%.
7. 5. The honeycomb structure according to claim 1, which is a catalyst carrier for supporting a selective catalytic reduction catalyst for exhaust gas purification in the pores of the partition walls.
8. 5. The honeycomb structure according to claim 1, wherein a selective catalytic reduction catalyst for purifying exhaust gas is supported in the pores of the partition walls, and a filling rate of the catalyst in the pores is 20 to 35%.
Citation Information
Patent Citations
Ceramic catalyst object
JP2008062216A
Honeycomb structure and honeycomb catalytic substance
JP2011194342A
Honeycomb structure
JP2016204208A
Honeycomb structure
JP2017171553A